2022
DOI: 10.1002/pmic.202100289
|View full text |Cite
|
Sign up to set email alerts
|

Improving the proteome coverage of Daphnia magna ‐ implications for future ecotoxicoproteomics studies

Abstract: Aquatic pollution is an increasing problem and requires extensive research efforts to understand associated consequences and to find suitable solutions. The crustacean Daphnia is a keystone species in lacustrine ecosystems by connecting primary producers with higher trophic levels. Therefore, Daphnia is perfectly suitable to investigate biological effects of freshwater pollution and is frequently used as an important model organism in ecotoxicology. The field of ecotoxicoproteomics has become increasingly prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Only seven studies of the entire data set analyzed whole-transcriptome expression profiles (using RNA-seq). Besides RNA-seq, proteomics is also rapidly developing for Daphnia as a powerful research tool [ 122 ].…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Only seven studies of the entire data set analyzed whole-transcriptome expression profiles (using RNA-seq). Besides RNA-seq, proteomics is also rapidly developing for Daphnia as a powerful research tool [ 122 ].…”
Section: Experimental Approachesmentioning
confidence: 99%
“…In this issue of Proteomics , Wilde and collaborators [8] propose the use of tandem mass spectrometry operated in data‐independent analysis mode to obtain comprehensive coverage of the proteome of the crustacean Daphnia magna , a miniaturized relevant model for aquatic ecotoxicology [9]. It has been demonstrated that this sophisticated method applies well to such species, even if the biological material is only available in limited quantity and the dynamic range of the proteome is quite unfavorable.…”
mentioning
confidence: 99%